Pengaruh January Effect Terhadap Return Saham IHSG di Bursa Efek Indonesia - RINI IRAWAN (EKBIS (Ekonomi & Bisnis), 2021)
Abstract. This study aims to examine the existence of the January Effect on the stock returns of JCI that occurred during the study period. The study was conducted on the composite stock price index on the Indonesia Stock Exchange during the 2016-2021 period. Hypothesis testing is carried out with Autoregressive conditional heteroskedasticity, where the results show the January effect seen in 2017 and 2021. Keywords. ARCH; January Effect; JCI stock returns.